Proceedings of the Seventh International Conference on Languages and Arts (ICLA 2018) 2019
DOI: 10.2991/icla-18.2019.103
|View full text |Cite
|
Sign up to set email alerts
|

Realization of Negative Politeness Strategy on Speech Act of Questions and Answers in the Learning Processes

Abstract: Research on the use of negative politeness strategies in speech acts has often been done, but the realization of strategies that speak with negative politeness in speech acts to ask and answer in the classroom learning process by teachers and students has not been fully explained. This article was written to explain the realization of the strategy of speak act with negative politeness in Indonesian which is done by teachers and students in the classroom learning process. This article's data is a speech act of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 4 publications
0
5
0
Order By: Relevance
“…Indirect conventionally has the effect of reducing the level of coercion on speech partners so that speech is felt enough polite by the speech partners (Leech, 1983), (Blum-Kulka, 1987), (Brrown and Levinson, 1987), (Manaf, 2017). Clause ... karena ada meja ini ... (because there is a table) in the speech (5), this clause ruangan ini menjadi sempit (the room become narrow) in the speech ( 6) is an element forming the indirectness of conveying the meaning to the speech partner. The constituent element of the indirectly of the delivery of the message in the form of this clause is indirect inconventionally, which is open in its form that goes beyond the boundaries of the grammatical convention and its meaning exceeds the limits of a semantic convention so that message delivery is too indirect.…”
Section: Polite Enough Speech Actmentioning
confidence: 99%
See 2 more Smart Citations
“…Indirect conventionally has the effect of reducing the level of coercion on speech partners so that speech is felt enough polite by the speech partners (Leech, 1983), (Blum-Kulka, 1987), (Brrown and Levinson, 1987), (Manaf, 2017). Clause ... karena ada meja ini ... (because there is a table) in the speech (5), this clause ruangan ini menjadi sempit (the room become narrow) in the speech ( 6) is an element forming the indirectness of conveying the meaning to the speech partner. The constituent element of the indirectly of the delivery of the message in the form of this clause is indirect inconventionally, which is open in its form that goes beyond the boundaries of the grammatical convention and its meaning exceeds the limits of a semantic convention so that message delivery is too indirect.…”
Section: Polite Enough Speech Actmentioning
confidence: 99%
“…Researchers who conducted research on the politeness of the young generation of high school students were Masfufah and Nurul (2012) [1], Lestariani, Martha, and Putrayasa (2014) [2], Musyawir (2017) [3], Astuti, Widodo HS and Sunoto (2017) [4], Abdurrahman and Manaf (2018) [5], Cahyaningrum, Andayani and Setiawan (2018) [6], Lindayana, Arifuddin, Mandala (2018) [7]. The research was conducted without paying attention to the ethnic aspects of a school.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Directive speech acts are speech acts that threaten the "face" (self-image of the doer) so that many researchers are called to teach it [2]. People who have done research politeness multiethnic learner is Ali (2011) [3], Masfufah (2012) [4], Ardhiarta (2013) [5], Afriansyah (2016) [6], Arta (2016) [7], Noor dan Prayitno (2016) [8], Abdurrahman (2017) [9], Musyawir (2017) [10], Nurjanah (2017) [11], Sahlullah (2017) [12], Alika (2011) [13], Kurniadi, Hilaliyah (2018) [14], Cahyaningrum (2011) [15], Febriadina (2017) [16], Jamaluddin (2018) [17], Widiadnya, Seken, Santosa (2018) [18], Lindayana, Arifuddin, Mandala (2018) [19], Cahyaningrum, Andayani dan Setiawan (2018) [20], Abdurrahman dan Manaf (2018) [21]. Ali (2011) research is the politeness imperative interaction son Madrasah Aliyah students of Class X was typical [9].…”
Section: Introductionmentioning
confidence: 99%
“…Cahyaningrum, Andayani and Setiawan (2018) found Surakarta students used a strategy tells different in me response to an act of speech are the same [20]. Abdurrahman and Manaf (2018) found that teachers often use negative politeness in the form of minimizing coercion and providing alternative choices when asking students in the teaching and learning process in class so that students are comfortable in discussing [21]. Based on tracing the results of previous research that are relevant to this research until 2018 above, there has been no research result in the form of a formulation of the level of courtesy of directive speech acts, especially ordering in Indonesian to multi-ethnic Madrasah Aliyah students who live in Padang.…”
Section: Introductionmentioning
confidence: 99%